Coordinated Motion Control of Autonomous and Semiautonomous Mobile Agents - Qing-Quan Liu (Institute of Advanced Engineering and Science, 2012)
This paper addresses networked control problems which arise in the coordinated motion control of autonomous and semiautonomous mobile agents, where the sensors and controllers are geographically separated and connected by digital communication channels carrying a finite number of bits per unit time. Different from the existing results, this case with quantized output measurements and limited data rates is considered. A quantization, coding and control scheme is presented under communication constraints. In particular, it is shown that the unstable plant may be stabilizable in the mean square sense if the data rate of the channel is greater than the lower bound proposed in our results. Simulation results show the validity of the proposed scheme. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1192